Workshop Marketplace System Using Rajaongkir API, Leaflet API and Midtrans Payment Gateway - Arta, Ketut Nila; Sudana, A.A Kompiang Oka; Putri, Gusti Agung Ayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The automotive shop is a business engaged in the automotive sector that serves vehicle repairs and sales of various kinds of vehicle spare parts. A marketplace is a place for buying and selling or a market that uses internet media. The current marketplace is still very common, making it difficult to find a marketplace that focuses on the automotive sector and difficult to find information about available automotive shops around. The automotive shop marketplace system can help to carry out the process of buying and selling vehicle spare parts and assist in finding various spare parts and information about available automotive shops based on the user's location. This system was developed on a web-based basis using the PHP programming language with the Laravel framework and integrated with the Leaflet API, RajaOngkir API, and Midtrans Payment Gateway as additional features in creating a marketplace. The leaflet API displays a map containing the location of the automotive shop listed on the marketplace. RajaOngkir API provides information about shipping costs to the buyer's place from the seller's place. Midtrans Payment Gateway bridges the payment process carried out by both parties so that it can take place properly. The method used in this research is to use the System Development Life Cycle (SDLC) waterfall method. The results of the research conducted were tested using the black-box method.